2019
DOI: 10.1152/jn.00576.2018
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical study of velocity fluctuations during slow movements in humans

Abstract: Moving smoothly is generally considered as a higher-order goal of motor control and moving jerkily as a witness of clumsiness or pathology, yet many common and well-controlled movements (e.g., tracking movements) have irregular velocity profiles with widespread fluctuations. The origin and nature of these fluctuations have been associated with the operation of an intermittent process but in fact remain poorly understood. Here we studied velocity fluctuations during slow movements, using combined experimental a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(59 citation statements)
references
References 93 publications
0
59
0
Order By: Relevance
“…Taken together, these experiments suggested that, firstly, performing movements at a low speed induces particular constraints on motor control (Guigon et al 2019) and that, secondly, there is a lower limit for the regulation of the frequency of rhythmic movements. Consistent with these findings, Levy-Tzedek also found "that specific combinations of required movement frequency and amplitude give rise to two distinct types of movements: one of a more rhythmic nature, and the other of a more discrete nature" (Levy-Tzedek et al 2010).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Taken together, these experiments suggested that, firstly, performing movements at a low speed induces particular constraints on motor control (Guigon et al 2019) and that, secondly, there is a lower limit for the regulation of the frequency of rhythmic movements. Consistent with these findings, Levy-Tzedek also found "that specific combinations of required movement frequency and amplitude give rise to two distinct types of movements: one of a more rhythmic nature, and the other of a more discrete nature" (Levy-Tzedek et al 2010).…”
Section: Discussionmentioning
confidence: 84%
“…It is now understood that discrete and rhythmic movements are on the same continuum and that the transition from one to the other is speed dependant (Hogan and Sternad 2007). A recent study showed that slow movements, whether discrete (Guigon et al 2019) or rhythmic (Park et al 2017;van der Wel et al 2010) are less regular and involve different control mechanisms. Levy-Tzedek studied how movement amplitude and frequency were modulated together in the voluntary control of movement speed during a rhythmic task (Levy-Tzedek et al 2011;Levy-Tzedek et al 2010).…”
Section: General Introductionmentioning
confidence: 99%
“…In order to better understand this modulation we built four normative models using OFC: a classical finite-horizon OFC (Liu and Todorov (2007)), a finite-horizon time-to-target adjusted OFC, a receding-horizon OFC (Guigon et al (2019)) and an infinite-horizon OFC (Qian et al (2013)). While the classical, receding and infinite horizon models failed to predict the experimental visuomotor feedback response intensities, the time-to-target model qualitatively replicated the visuomotor feedback intensity profile of our participants.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to our finite horizon control we also implemented a receding horizon controller (Guigon et al (2019)).…”
Section: Receding Horizon Ofcmentioning
confidence: 99%
“…2C shows that the correlation of signed deviation between TG and HP over all subjects drastically decreases with increasing stiffness. In contrast, the correlation between RP and HP only slightly decreases probably due to the oscillations of force in HPs [19]. The high correlation between the HPs and the RP indicates that the user deviates in the same way when interacting with either of these partner conditions.…”
Section: A Performancementioning
confidence: 93%